2010
DOI: 10.4238/vol9-3gmr884
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic and entomopathogenic strains of Beauveria sp to control the bovine tick Rhipicephalus (Boophilus) microplus

Abstract: ABSTRACT. Pathogenicity of strains of the entomopathogenic fungus Beauveria bassiana and endophytic strains of Beauveria sp against the bovine tick Rhipicephalus (Boophilus) microplus was tested in laboratory bioassays and under field conditions. Suspensions containing 10 5 , 10 7 and 10 9 conidia/mL were prepared of each fungal strain for laboratory bioassays. The ticks were maintained at 28°C, 90 ± 5% relative humidity, and the following variables were evaluated: initial female weight, egg weight, hatching p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
0
17
1
1
Order By: Relevance
“…It was known that tick larvae were the most susceptible than other stages (Camargo et al, 2012). The present result is similar to those reported by Cafarchia et al, (2015) but they encountered 100% mortality of larvae at 15 days PA. On other hand, several studies reported lower mortalities rates than the rate of present study (Kaaya and Hassan 2000;Reis et al, 2005;Campos et al, 2010). We think that the technique of application, larval age and tick species may be the causes of this variation.…”
Section: March 2018 | Volume 6 | Issue 3 | Page 144contrasting
confidence: 46%
“…It was known that tick larvae were the most susceptible than other stages (Camargo et al, 2012). The present result is similar to those reported by Cafarchia et al, (2015) but they encountered 100% mortality of larvae at 15 days PA. On other hand, several studies reported lower mortalities rates than the rate of present study (Kaaya and Hassan 2000;Reis et al, 2005;Campos et al, 2010). We think that the technique of application, larval age and tick species may be the causes of this variation.…”
Section: March 2018 | Volume 6 | Issue 3 | Page 144contrasting
confidence: 46%
“…Moreover, we found that the mortality rate reached 55.25% at only 6 days after inoculation with 10 8 Beauveria conidia mL −1 . Likewise, when R. microplus were treated with B. bassiana and M. anisopliae (Campos et al 2010;Frazzon et al 2000), the most virulent strains were able to induce mortality in up to 50% of the tick population by 7 and 5 days after treatment, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Estos estudios coinciden con el presente, respecto a la eficacia de lo cual varía dependiendo de la cepa y la concentración utilizada. Según Frazzon et al (2000), Kirkland et al (2004) y R.A. Campos, et al (2010), esta diferencia en la eficacia depende de la capacidad de la cepa del hongo para penetrar la cutícula de la garrapata, usando una combinación de mecanismos enzimáticos y físicos. No obstante, aunque se cuenta con un considerable volumen de información sobre estudios realizados con Metarhizium anisopliae para el control de garrapatas Ricephalus (Boophilus) microplus, no ocurre lo mismo para el hongo de Beauveria bassiana, del cual, a excepción del trabajo publicado por Ren et al (2011), donde evalúa la virulencia de varias cepas chinas de este hongo, se cuenta con poca información específica publicada para el control de garrapatas Ricephalus (Boophilus) microplus.…”
Section: Discussionunclassified